Answer:
3(2+15)= 3(2) + 3(15)
Step-by-step explanation:
Answer:
yes
Step-by-step explanation:
Answer:
531441
Step-by-step explanation:
We can find by factorization
531441 = 9 * 9 * 9 * 9 * 9 *9 = (9*9*9) * (9*9*9)
![\sqrt[3]{531441}=\sqrt[3]{9*9*9*9*9*9} =9*9 = 81\\\\\\\sqrt{531441}=\sqrt{(9*9)*(9*9)*(9*9)}=9*9*9=729](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7B531441%7D%3D%5Csqrt%5B3%5D%7B9%2A9%2A9%2A9%2A9%2A9%7D%20%20%3D9%2A9%20%3D%2081%5C%5C%5C%5C%5C%5C%5Csqrt%7B531441%7D%3D%5Csqrt%7B%289%2A9%29%2A%289%2A9%29%2A%289%2A9%29%7D%3D9%2A9%2A9%3D729)
Answer: The value of 'h' is 3.
Step-by-step explanation: Given that the vertex form of a function is given by
![g(x)=a(x-h)^2+k~~~~~~~~~~~~~~~~~~~~~~~~(i)](https://tex.z-dn.net/?f=g%28x%29%3Da%28x-h%29%5E2%2Bk~~~~~~~~~~~~~~~~~~~~~~~~%28i%29)
We are to find the value of 'h' when the following function is converted to the vertex form.
![g(x)=x^2-6x+14~~~~~~~~~~~~~~~~~~~~~~(ii)](https://tex.z-dn.net/?f=g%28x%29%3Dx%5E2-6x%2B14~~~~~~~~~~~~~~~~~~~~~~%28ii%29)
From equation (ii), we have
![g(x)=x^2-6x+14\\\\\Rightarrow g(x)=x^2-2\times x\times 3+3^2-3^2+14\\\\\Rightarrow g(x)=(x-3)^2-9+14\\\\\Rightarrow G(x)=(x-3)^2+5.](https://tex.z-dn.net/?f=g%28x%29%3Dx%5E2-6x%2B14%5C%5C%5C%5C%5CRightarrow%20g%28x%29%3Dx%5E2-2%5Ctimes%20x%5Ctimes%203%2B3%5E2-3%5E2%2B14%5C%5C%5C%5C%5CRightarrow%20g%28x%29%3D%28x-3%29%5E2-9%2B14%5C%5C%5C%5C%5CRightarrow%20G%28x%29%3D%28x-3%29%5E2%2B5.)
Comparing it with the vertex form (i), we get
![h=3.](https://tex.z-dn.net/?f=h%3D3.)
Thus, the value of 'h' is 3.
Perimeter 430
Length 172
172 next
430 last(after the =)